Evaluation of Essential and Emergency Surgery Provide in Primary Hospitals of Gedeo Zone and Sidama Region, South, Ethiopia, 2020 - Regasa T; Zemedkun A; Neme D (Open Access Emergency Medicine, 2022)
Teshome Regasa, Abebayehu Zemedkun, Derartu Neme Anesthesiology Department, Dilla University, Dilla, EthiopiaCorrespondence: Teshome Regasa, Tel +251 910563710, Email regasateshe32@gmail.comBackground: Surgical services at level referral hospitals were an essential part of overall health care. The surgical uhservice was approximated to account for 11% of the worldwide load of disease, with a large percentage of that burden being uncovered in resource-constraint settings. Even though the surgery service is significant and growing across all economic sectors, the majority of resource-limited countries have been unable to provide essential surgical services.Objective: To investigate the capacity of essential and emergency surgical services in primary hospital facilities in the Gedeo zone and Sidama region.Methodology: In the Gedeo zone and Sidama region, a cross-sectional study was undertaken in eight district hospitals. By looking at four areas of data: infrastructure, human resources, interventions available, and equipment, a World Health Organization tool for conditional analysis was used to assess a health set-up competence to perform essential surgical and anesthetic procedures. The tool looked for eight different categories of healthcare giving 35 surgical procedures, and 67 different pieces of instruments.Results: This research found that 48.57% of the 35 essential interventions counted in the test, including cesarean section, were available at all hospitals. Prior to admission, each hospital reported a total of 53 beds, with an average travel distance of 28 kilometers. There were 189 healthcare providers in the eight facilities. According to the research, basic instruments were not always present at all of the sites.Conclusion: Infrastructure, health profession, service supply, and key instruments and supplies deficiencies reveal major inadequacies in hospitals’ capacity to perform EESC and efficiently treat the growing surgical load of disease and damage in primary care.Keywords: burden of emergency surgery, emergency and essential surgery, emergency and urgent surgical treatment